KERJASAMA ILO DAN INDONESIA DALAM PERLINDUNGAN PEKERJA MIGRAN INDONESIA DI MALAYSIA LEWAT PROGRAM DECENT WORK COUNTRY PROGRAMMES(DCWP) - Ilham Zico Pratama (UIR Press, 2020)
The state is obliged to guarantee rights, opportunities, and provide protection for every citizen without discrimination to get decent work and income, both at home and abroad in accordance with their expertise, skills, talents, interests and abilities. So far, the government seems to be less serious about protecting migrant workers, resulting in cases of human trafficking, slavery, forced labor, victims of violence, abuse, crimes against human dignity, and other treatments that violate human rights. For this reason, international cooperation is carried out to ensure the safety of Indonesian Migrant Workers (IRC). One of the collaborations carried out is the collaboration between Indonesia and the International Labor Organization (ILO). Decent Work Country Program (DCWP) which serves to protect PMI in Malaysia, as one of the countries that receives the most migrant workers from Indonesia.